(untitled) (Journal of Forensic Medicine & Toxicology, 2021)
Events of violence against married women has increased. In India female have suffered violence at the hands of their husband and his family members. Present study was conducted on dead bodies brought for the purpose of post-mortem examination during the period of January 2016 to December 2016 at Department of Forensic Medicine, P.D.U. Govt. Medical College & Hospital, Rajkot. The present study has been carried out to realize the social, ethical and medico-legal aspects of death of married women due to poison, putting sincere efforts to establish the various factors responsible for the same and thereby to plan successful preventive measures to curb the menace of unnatural death of married women. The present study clearly points out that incidence of unnatural death of married women due to poison was frequently observed in study group like low educated, young age, house-wives from joint families and those belong to poor socioeconomic status.